2023
DOI: 10.3390/toxins15020098
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues on Tropane Alkaloid Contamination of Food in Europe

Abstract: The occurrence of tropane alkaloids (TAs), toxic plant metabolites, in food in Europe was studied to identify those TAs in food most relevant for human health. Information was extracted from the literature and the 2016 study from the European Food Safety Authority. Calystegines were identified as being inherent TAs in foods common in Europe, such as Solanum tuberosum (potato), S. melongena (eggplant, aubergine), Capsicum annuum (bell pepper) and Brassica oleracea (broccoli, Brussels sprouts). In addition, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Atropine and scopolamine are two natural toxins from the tropane alkaloid (TA) family that are of great concern due to reports of their occurrence in food poisoning events [ 1 , 2 , 3 , 4 , 5 ]. TAs are a large family of alkaloids consisting of more than 200 identified molecules [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Atropine and scopolamine are two natural toxins from the tropane alkaloid (TA) family that are of great concern due to reports of their occurrence in food poisoning events [ 1 , 2 , 3 , 4 , 5 ]. TAs are a large family of alkaloids consisting of more than 200 identified molecules [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The population is exposed to these natural toxins through food, usually of plant origin, although some studies have reported the transfer of TAs to animal foods, such as honey and milk [ 3 , 8 ]. Cereals and pseudocereals are the most contaminated foods [ 11 , 12 , 13 , 14 , 15 ], followed by teas, herbal teas [ 16 , 17 , 18 , 19 , 20 ], spices [ 21 ], honey [ 22 , 23 ], and vegetables [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations